Assessment of the protective effect of carbonation on portlandite crystals. (August 2015) - Galan, I.; Glasser, F.P.; Baza, D.; Andrade, C.
Abstract: The kinetics of many reactions important to cement hydration and use are not well understood: this is in part due to the great complexity of many supposedly "simple" processes. One such process, carbonation of portlandite, Ca(OH)2, in moist air at ~ 23 °C has been investigated by microscopy and microchemical analysis. Single crystals of portlandite were grown, carbonated at relative humidities between ~ 25 and ~ 90%, and the transport properties of the self-generated calcite, CaCO3, product film were determined. The calcite films thus grown within days or weeks varied in thickness but typically were polycrystalline and epitaxial: a variety of morphologies and surface features are recorded. Permeation was measured by determining the time taken for Ca 2 + ions, arising from the Ca(OH)2 substrate, to diffuse through the calcite coat into initially pure water. The spontaneous formation of self-protecting films on concrete has long been envisaged: results demonstrate that passivation can actually be achieved.